C4 vegetation characteristics in the monsoon rainforest of the Pearl River delta during the MIS 2 period. (November 2022) - Niu, Dongfeng; Wang, Fengnian; Shu, Peixian; Li, Baosheng; Si, Yuejun; Wen, Xiaohao; Chen, Min; Wang, Chen; Liu, Longlong
Highlights: Millennial-scale C3/C4 ecosystem changes in the Pearl River delta plain studied. Three major C4 grassland expansions/decreases of monsoon rainforest landscape identified inMIS 2. Changes of plant ecosystems closely tracked rainfall records in southern subtropical China. Abstract: The impact of abrupt climate change during glacial periods on terrestrial ecosystems are widely acknowledged by paleoecology and paleoclimate communities as key issues in the ongoing debate on geographical distribution and patterns of genetic diversity of species. However, the C4 plant expansion in subtropical South China at the mouth of the Pearl River during the glaciated Marine Isotope Stage 2 (MIS 2) in response to millennial-scale climate changes is largely unknown. In this study we present results of the isotopic composition of sediment organic carbon (δ 13 CTOC ) obtained from a high-resolution fluvial sequence from the Pearl River delta plain in southern China to show millennial-scale C3 /C4 ecosystem changes during the MIS 2 interval. Three major C4 grassland expansions and declines of the monsoon rainforest landscape are identified during the MIS 2 period. Our results reveal that during MIS 2 δ 13 CTOC values shifted profoundly from about −29 ‰ to enriched values of up to −17 ‰ three times and we interpret these as due to episodic expansions of the C4 plants to form a mixed C3 /C4 plant ecosystem with the collapse of a pure C3 monsoon rainforest community in this region. These drastic expansions of C4 ecological systems occurred at 24.8–24 ka, 23.8–21 ka, and 18–15.6 ka cal BP intervals, equivalent to well-known Heinrich Stadial (HS) 2, Last Glacial Maximum (LGM), and HS1 super-cold Northern Hemisphere intervals. We found that these drastic changes of plant ecosystems closely tracked the monsoon records during the significant weakening of Asian Summer Monsoon Intervals (WSMIs) of the MIS 2 period.